Sustainability-oriented Service Innovation: fourteen-year longitudinal case study of a tourist accommodation provider. Issue 10 (3rd October 2018) - Warren, Christopher; Becken, Susanne; Coghlan, Alexandra
Abstract: Progressing sustainable tourism requires both an innovative transition from "unsustainable" tourism and innovative research methods to develop theory and concepts for a sustainable tourism. While there are many ad hoc examples of initiatives, there are very few examples of firms systematically recording their medium-term evolutionary progress. This case study of an accommodation provider uses longitudinal data over 14 years, deductive and inductive methods, and comparison with other similar eco-friendly providers, to provide the first exploration of sustainability-oriented innovation by a firm attempting to make transitions. Findings show how important hindsight and insight are for continuous learning, and how broader community sustainability issues influence the owners' worldviews. Both learning and changing views are required to support innovation. A Sustainability-oriented Service Innovation model is recommended, recognising the characteristics of a service industry where innovation can be an organic process led by humans for humans and consequently more fuzzy in its progress than the clearly defined steps that are suggested by previous research. This model seeks to assist researchers and practitioners to better measure innovative progress of service firms, and develop more relevant strategies to ease transitions towards sustainable business practices.